2008
DOI: 10.1590/s0101-41612008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Existe influência da ideologia sobre o resultado fiscal dos governos estaduais brasileiros?

Abstract: Resumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
3
8
1
12
Order By: Relevance
“…Even though the study objectives were different, our result differs from that observed by Arvate, Avelino and Lucinda (2008), who found empirical evidence of the influence of political ideology of state governors in obtaining better fiscal balances. They found that right-wing governors produced better fiscal balances by generating greater revenue.…”
Section: Analysis Of the Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Even though the study objectives were different, our result differs from that observed by Arvate, Avelino and Lucinda (2008), who found empirical evidence of the influence of political ideology of state governors in obtaining better fiscal balances. They found that right-wing governors produced better fiscal balances by generating greater revenue.…”
Section: Analysis Of the Resultscontrasting
confidence: 99%
“…Despite this counterintuitive result, it does corroborate the findings of Arvate, Avelino and Lucinda (2008), who observed that governors of the same party as the president did not have greater ease in the execution of the governmental budget.…”
Section: Analysis Of the Resultssupporting
confidence: 80%
See 3 more Smart Citations